Advancements of AI in healthcare: a comprehensive review of ChatGPT’s applications and challenges - Ali, Sara; Aslam, Atrubah; Tahir, Zarmeen; Ashraf, Bashair; Tanweer, Afifa (Journal of the Pakistan Medical Association, 2024)
The rapid integration of artificial intelligence into healthcare has introduced transformative possibilities and challenges. The current narrative review was planned to explore diverse applications of Chat Generative Pre-Trained Transformer (ChatGPT) across medical domains, ranging from dietary planning and disease management to medical education and clinical decision support. A comprehensive analysis of ChatGPT’s healthcare applications was conducted between July and September 2023, reviewing literature from prominent medical journals and databases, including PubMed, Embase, Cochrane library and the Cumulated Index in Nursing and Allied Health Literature. The studies revealed notable limitations, including inaccuracies, bias and potential safety concerns. Quantitative data highlighted ChatGPT’s high accuracy rates in disease detection, nutrient sufficiency in ChatGPT-generated diet plans and various medical scenarios. The predominantly quantitative evaluations might overlook nuanced qualitative aspects, such as users’ perceptions, experiences and ethical concerns. Studies often focus on specific domains, potentially limiting generalisability. —Continue